2014
DOI: 10.1115/1.4026370
|View full text |Cite
|
Sign up to set email alerts
|

Convective Condensation Inside Horizontal Smooth and Microfin Tubes

Abstract: An experimental investigation was performed for convective condensation of R410A inside one smooth tube (3.78mm, inner diameter) and six microfin tubes (4.54, 4.6 and 8.98 mm, fin root diameter) of different geometries for mass fluxes ranging from 99 to 603 kg m~^s~'. The experimental data were analyzed with updated flow pattern maps and evaluated with existing correlations. The heat transfer coefficient in the microfin tubes decreases at first and then increases or flattens out gradually as mass flux decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Verification of the test apparatus for single-phase flow and two-phase flow in smooth tubes was previously performed by Wu et al [8]. Using the same experimental set up, Wu et al [23] studied the heat transfer enhancement mechanism in microfin tubes and found that the enhancement is mainly due to the surface area increase at large mass fluxes; additionally they found that liquid drainage by surface tension and interfacial turbulence enhance heat transfer greatly at low mass fluxes. Li et al [24] found a nonlinear relation between mass flux and the condensation heat transfer coefficient.…”
Section: Methodsmentioning
confidence: 94%
“…Verification of the test apparatus for single-phase flow and two-phase flow in smooth tubes was previously performed by Wu et al [8]. Using the same experimental set up, Wu et al [23] studied the heat transfer enhancement mechanism in microfin tubes and found that the enhancement is mainly due to the surface area increase at large mass fluxes; additionally they found that liquid drainage by surface tension and interfacial turbulence enhance heat transfer greatly at low mass fluxes. Li et al [24] found a nonlinear relation between mass flux and the condensation heat transfer coefficient.…”
Section: Methodsmentioning
confidence: 94%
“…The heat transfer coefficients for the condenssing flow obtained using the models described before are compared with the experimental data in our previous experimental studies [39]. More details about the experimental setup and data reduction can be found in Wu et al [39].…”
Section: Comparison Of Numerical Data With Experimental Results and Ementioning
confidence: 99%
“…More details about the experimental setup and data reduction can be found in Wu et al [39]. The local numerical heat transfer coefficients are also compared with empirical correlations developed by Cavallini et al [38], Thome et al [41], Shah [42].…”
Section: Comparison Of Numerical Data With Experimental Results and Ementioning
confidence: 99%
“…No previously reported condensation or evaporation data exists for the enhanced geometry considered in this study (Vipertex 1EHT tube); therefore a comparison of the 1EHT tube performance will be made to smooth tube. As indicated in Wu et al [40,41], helical micro-fin tubes are more effective at low mass fluxes due to the strong surface tension effects that are seen at low mass fluxes. Therefore, the focus of the current experimental investigation will be on low mass fluxes.…”
Section: Introductionmentioning
confidence: 89%
“…Heat flux was obtained from the inlet and exit water temperatures (measured using platinum RTDs). Flow rate is controlled by a valve located after [42] and Wu et al [41]. For enhanced tubes, there are limited heat transfer predicting procedures available with the degree of confidence necessary to perform relevant designs; any work that has been done is limited to the specific geometry and operating conditions based upon tests from which the predicting procedures have been derived.…”
Section: Experimental Apparatusmentioning
confidence: 99%